Assessment of growth and maternal attitude towards feeding practices in children with cleft lip and palate - Gopinath, V.K. (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2003)
Cleft lip and palate (CLP) are one of the commonest congenital abnormalities, which occur in early pregnancy. Congenital cleft results in a gap involving the lip, the upper maxilla and the palate, either independently or in combination. The majority of cleft appears to be due to a combination of genetics and environmental factor. Epidemiological studies conducted on the incidence of cleft palate and lip in Malaysian preschool children showed 1: 1304 for cleft lip and 1:1594 for cleft palate (1), while international data showed craniofacial anomalies occurs in approximately 1 in 500 live birth (2). Patients with cleft lip and palate present with a number of problems among them feeding difficulties is commonly observed and is the most traumatic experience the family has to face. Children especially those with a cleft palate, have impaired sucking mechanism. More specifically, despite adequate sucking movements, they are unable to generate the negative pressure required for adequate sucking to occur (3,4). More air than normal is swallowed, feeding takes longer and the child may tire before the completion of the feed (3,5). These children are prone to nutritional problems since the healthiest and the safest source of nutrition for infants in breast milk. Recurrent infections, repeated operations and adverse psychosocial influences further aggravate the problem. These infants are undernourished and have a compromised growth in the early months after birth ( 6, 7). The growth problems of children with orofacial clefts have largely been attributed to inadequate nutrition (S).However, studies have shown many children with orofacial clefting have impaired growth with no impairment of weight gain (9). Hence assessment of growth in children with orofacial cleft is crucial because it may be treatable in the early stages. The purpose of this study was to 1) to assess general health and growth parameters in children with CLP and those of normal children. 2) to investigate the feeding methods of CLP infants and normal infants. 3) to assess the maternal attitude towards breast - feeding 5